2021
DOI: 10.3389/fpsyt.2021.773604
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Mediated Interventions for Children and Adolescents With Autism Spectrum Disorders: A Systematic Review and Meta-Analysis

Abstract: There has been increasing interest in parent-mediated interventions (PMIs) for children with autism spectrum disorders (ASDs). The objective of this systematic review and meta-analysis was to examine the effect of PMIs compared to no PMI for children with ASD aged 2–17 years. The primary outcome was adaptive functioning rated by a parent or clinician. The secondary outcomes were long-term adaptive functioning rated by the parents, adverse events, core symptoms of ASD, disruptive behavior, parental well-being, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 70 publications
1
16
0
1
Order By: Relevance
“…Therefore, various play-based interventions have been developed and used to support the social communication and language needs of autistic children [11][12][13][14][15][16][17][18][19]. Although many reviews and meta-analyses have reported the characteristics and overall effectiveness of play-based interventions on autistic children's social communication and language skills [39,51,[54][55][56][64][65][66][67][68][69][70][71][72][73], to the best of the authors' knowledge, the current study will be the first to evaluate the effectiveness of parent-mediated play-based interventions conducted in non-educational settings on the social communication and language skills of preschool autistic children. Hence, the review will shed new light on the role of parental mediation in the effectiveness of play-based interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, various play-based interventions have been developed and used to support the social communication and language needs of autistic children [11][12][13][14][15][16][17][18][19]. Although many reviews and meta-analyses have reported the characteristics and overall effectiveness of play-based interventions on autistic children's social communication and language skills [39,51,[54][55][56][64][65][66][67][68][69][70][71][72][73], to the best of the authors' knowledge, the current study will be the first to evaluate the effectiveness of parent-mediated play-based interventions conducted in non-educational settings on the social communication and language skills of preschool autistic children. Hence, the review will shed new light on the role of parental mediation in the effectiveness of play-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Since Phase I comprises the studies that were published between 2000 and January 2021, an additional search for relevant studies published in 2021 will be carried out on the aforementioned databases and by using the same search strings (S2 Table in S1 File ). The database search will be conducted by the first author (ED) alongside a comprehensive citation search of the previous systematic review and meta-analysis on parent-mediated interventions in autism [ 39 , 51 , 54 56 , 64 73 ]. The identified studies will be merged and downloaded into Mendeley Reference Manager software for performing the title, abstract and full-text screenings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, caregivers play an active role in their child's treatment and interventions can be individually adapted. Though methodologies vary, recent metaanalyses and studies demonstrate positive outcomes when involving caregivers as interventionists (Conrad et al, 2021;Nevill et al, 2018). Further, Liu and Schertz (2021) found that trained caregivers demonstrated high fidelity to intervention procedures, providing further support for reinforcing the caregiver's active role in the child's treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, literal interpretation of language and difficulty in understanding the intent of other people leads to behavioral challenges in some people with ASD and affects success in school, leisure activities, and employment ( 2 ). There has been increasing interest in parent-mediated interventions for children with ASD ( 11 ), as well as proof of their success. Reviews suggests that interventions conveyed by parents of children with ASD can improve communication of persons with ASD.…”
Section: Introductionmentioning
confidence: 99%